Fast convergence delayed signal cancellation method for sequence component separation - Cardenas, Roberto; Diaz, Matias; Rojas, Felix; Clare, Jon C. (IEEE, 2015)
Delayed Signal Cancellation (DSC) is one of the methods used to separate the negative and positive sequence components in unbalanced 34 systems. In this paper a DSC methodology with a fast convergence time is proposed and is shown that an improved separation of the positive and negative sequences is feasible. Experimental results are presented to demonstrate the performance of the proposed methodology.